1999
DOI: 10.1148/radiology.213.3.r99dc06715
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Edema and Associated Pain in Early Stage Osteonecrosis of the Femoral Head: Prospective Study with Serial MR Images

Abstract: The results of this study suggest that the combination of marrow edema of the proximal femur and focal osteonecrosis of the femoral head are strongly associated with hip pain in early stage osteonecrosis, even prior to collapse. Pain improvement usually parallels the resolution of edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 48 publications
3
78
1
4
Order By: Relevance
“…Compared with the asymptomatic population the prevalence of bone marrow edema lesions is greater in patients with increased Kellgren-Lawrence grade and subchondral bone may be a major contributor to OA pain [7][8][9]12]. As expected, the preoperative Kellgren-Lawrence OA grade showed an inverse relationship to the postoperative Tegner Lysholm score.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Compared with the asymptomatic population the prevalence of bone marrow edema lesions is greater in patients with increased Kellgren-Lawrence grade and subchondral bone may be a major contributor to OA pain [7][8][9]12]. As expected, the preoperative Kellgren-Lawrence OA grade showed an inverse relationship to the postoperative Tegner Lysholm score.…”
Section: Discussionsupporting
confidence: 58%
“…However, using the Tegner Lysholm grading system (Table 1), we found that 10 of the 22 patients had an outcome considered a treatment failure. Percutaneous calcium phosphate injection has a theoretical potential to become a widely used treatment option for patients with subchondral bone marrow edema lesions which are considered a major source of pain in patients with OA [7][8][9]12]. However, the 22 procedures performed at our institution showed only marginal success at short-term followup.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) is a comparatively sensitive diagnostic modality for early diagnosis of osteonecrosis (Vande Berg et al, 2006;Koo et al, 1999;Sakaia et al, 2000). However, unless reparative tissue appears in stage 1, conventional MRI is not believed to detect necrotic lesions in stage 0 of the ARCO (Association Research Circulation Osseous) international classification (Uberoi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is typified by an "inflammatory pattern" in MRI (low signal intensity in t1-W and high signal intensity in t2-W sequences). typical BMe histological features are not marked by intra or extracellular fluid effusion, but rather depending on the etiology, by fibrosis and inflammatory infiltrate which often reflects the occurrence of pain in the affected bone segment [2,3]. BMeS usually affects the epiphyses of weight-bearing joints-hip, knee, foot and ankle-although it may manifest itself as a "migratory" BMe with multiple episodes in different locations [4,5].…”
mentioning
confidence: 99%